Culinary precisions as a platform for interdisciplinary dialogue - Fooladi Erik; Hopia Anu (BioMedCentral, 2022)
Claims or specifications about cooking (in some literature referred to as ’culinary precisions‘) as found in recipes or as generally shared knowledge, permeate the world of food and cooking. The collection and study of these culinary precisions carries with it potential as a framework for research, not only in food science, but also in other disciplines such as social sciences and humanities, allowing for multidisciplinary approaches and cross-fertilization between a broad range of sciences. These precisions also allow for novel approaches to education at all levels, as shown through educational efforts in several countries as well as educational research. Finally, they provide a unique arena for the interaction between science and society. In the present report, we describe a recent initiative, ‘The Kitchen Stories Network’, with an open invitation for interested parties to collaborate across disciplines and across societal boundaries in order to collect and study such culinary precisions for the common benefit of sciences, education, other stakeholders such as businesses and non-governmental organizations, and society in general.